Analysis of Marketing Strategies in the context of Green Products - Jaggi, Pallavi; Rini (Gyan Management Journal, 2023)
Purpose - In the context of the consumer durables products business, transformational marketing tactics have been made possible by the implementation of holistic marketing in the era of Industrial Revolution 4.0. As a result of customers’ active involvement with marketers, the range of marketing methods has expanded in line with consumer knowledge of climate sensitivity, establishing the groundwork for environmentally friendly products. Green marketing makes it possible for businesses to create and sell environmentally friendly goods. Enhancing the company’s reputation, making it simple to reach a specific consumer group (Niche marketing), and most crucially, retaining its competitive edge. As consumers become increasingly conscious of the quality of the items, green products are intriguing topics to debate. Consumer education about product quality strives to promote environmental protection and health advantages. The decision of consumers to purchase green products is influenced by a variety of factors. In the context of green products in the consumer durables business, the current study emphasizes the fundamentals of marketing strategies and related techniques. Consumer durables encompass anything from FMCG to electronic devices (white and brown products).